Challenges Encountered by College Students in Research - Clarin, Analyn S.; Barosa, Maria Angelica G.; Suico, Chris Devine A.; Bazar, Jame S.; Galindo, Russel P.; Baluyos, Genelyn R. (PT ARRUS Intelektual Indonesia, 2025)
Research has always been considered one of the most challenging aspects of being a student. This study explored the challenges encountered by college students in conducting research in one of the higher education institutions in Ozamiz City during S.Y. 2023-2024. This study utilized a qualitative approach and adopted a case study research design. Purposive sampling was applied to 17 participants. Data elicitation was achieved through face-to-face, in-depth interviews that used a researcher made interview guide. Yin's approach suggests that three themes emerge from the data. These are the initiation, design, and execution phases, multifaceted challenges of students, navigation of methodological, ethical, and analytical challenges, and strategies for overcoming challenges to access literature, collect data, analyze, interpret, and communicate. The use of university resources and academic databases provides necessary information and support for accessing relevant literature and data. Clear communication and proactive problem-solving ensure that students can address issues promptly and make informed decisions. Together, these strategies significantly aid students in overcoming research obstacles.